Canine mycotic keratoconjuntivitis caused by Acremonium kiliense - Mendoza, Leonel (1985)
Mycotic keratoconjuntivitis caused by Acremonium kiliense in a German Shepherd bitch was diagnosed with the aid of laboratory tests. The dog presented with photophobia, tearing, corneal edema and reduction of the visual capacity. A thick white layer partially covered the right eye. The left eye showed irritation and small brown stains which were diagnosed as pigmentary keratitis. The initial treatment consisted of 2% yellow mercury oxide. Natamycin was used as final treatment. Seven days later, the natural brightness of the eye as well as the visual capacity were restored.